Among Portraits of Women: Accommodation and Resistance in the Camillian Novel (Revista do Centro de Estudos Portugueses, 2025)
The presence of the female figure in 19th century Portuguese Society is one of the recurring themes in the work of Camilo Castelo Branco, which provides material for countless studies that try to understand the camillian thought about women. This article intends to reflect on how camillian works presents an overview of the role of the female figure, now defying and resisting the power structures of a system dominated by patriarchy, now accommodating and submitting to violence and the imperatives of the society. When portraying women, Camilo Castelo Branco presents characters that reveal an increasing complexity throughout his work where these women’s actions, which alternate between accommodation and resistance, gain place and visibility. For such an analysis, the contributions of Michael Foucault (1988, 2006), Michelle Perrot (1998), Maria Rita Kehl (2016) and Jean Anyon (1990) will be fundamentally important.